PENGARUH KEPEMIMPINAN DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT INDOPROF D’PENYETZ SEJATI DI KOTA BATAM: Employee Performance; Incentives;Leadership. - Melissa Dwi Febriyani; Mauli Siagian (Universitas Putera Batam, 2020)
This study aims to determine the effect of leadership and incentives on employee performance at PT Indoprof D'Penyetz Sejati in Batam City by using a saturation sampling technique. The total of sample is 110. Instrument that used to collect data is questionnaire. By using validity and reliability test to test the quality of data, used analysis of linear and coefficient of determination (R2) to do the experiment of classic assumption and to test the effect, while using the t test and F test to testing the hypothesis with the help of SPSS version 23. The outcome of the coefficient of determination (R2) shows that the leadership and the incentive effect 21.6% towards employee performance. While it can be seen that leadership influences 18,4% and incentives affect -28,5% on employee performance from the multiple linear regression. The conclusion that is based on results of this research dan discussion are that leadership partially has a positive and significant effect on employee performance, incentives have a partially negative and significant effect on employee performance and simultaneously leadership and incentives have a significant effect on employee performance. Keywords: Employee Performance; Incentives; Leadership.